2017
DOI: 10.1016/j.jngse.2016.11.054
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental investigation of the interaction of natural and propagated hydraulic fracture

Abstract: 5Hydraulic fracturing is extensively used to develop unconventional reservoirs, such 6 as tight gas, shale gas and shale oil reservoirs. These reservoirs are often naturally 7 fractured. Presence of these natural fractures can have beneficial or detrimental 8 effects on the outcome of hydraulic fracturing operation. A proper study is 9 required to characterize these formations, and design a suitable hydraulic 10 fracturing operation. 11 112Reservoir rock may contain imperfections such as faults, joints, natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(38 citation statements)
references
References 11 publications
1
31
0
Order By: Relevance
“…Lee et al (2015) utilized naturally fractured Marcellus shale rocks to conduct unconfined compressive strength (UCS) and SCB tests. Fatahi et al (2017) and Wang et al (2018b) coupled numerical and experimental approach to study propagating HF interaction with pre-existing NF. The authors' experimental results were converted to field scale using numerical methods.…”
Section: Methods Of Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee et al (2015) utilized naturally fractured Marcellus shale rocks to conduct unconfined compressive strength (UCS) and SCB tests. Fatahi et al (2017) and Wang et al (2018b) coupled numerical and experimental approach to study propagating HF interaction with pre-existing NF. The authors' experimental results were converted to field scale using numerical methods.…”
Section: Methods Of Approachmentioning
confidence: 99%
“…At low (20°) approach angle, the right side of a propagating dual-winged HF was arrested at NF interface, while the left side of the HF will deflect fluid into the proximate NF after intersection. When the angles between the NF plane and the maximum horizontal stress direction decrease, the HF will get arrested at the NF plane (Wang et al 2018a;Fatahi et al 2017). Olson et al (2012) concluded from a hydrostone block experiment results that oblique HF-NF intersections will lead to arrest or diversion of the propagating HF along the NF interface at sub-orthogonal.…”
Section: Arrest Of Hfmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Zhang et al 38 combined PFC and FLAC to study the behavior of a hydraulic fracture crossing natural fractures. Fatahi et al 39 investigated the interaction mechanisms of HF and NF by using PFC2D. DEM may be useful for understanding the mechanisms of intersection behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the effect of perforation erosion, Long and Xu 37 formulated a DDM approach to model the simultaneous propagation of multiple hydraulic fractures. Fatahi et al 39 investigated the interaction mechanisms of HF and NF by using PFC2D. However, the crossing criterion may begin to lose effectiveness under complex fracture network condition, because the local stress field varies due to the opening or shear slip of surrounding fractures.…”
mentioning
confidence: 99%